Theoretical Study of Mixed Hydrogen and Dihydrogen Bond Interactions in Clusters - Abedien Zabardasti; Nahid Zare; Masoumeh Arabpour; Ali Kakanejadifard; Mohammad Solimannejad (Journal of Chemistry)
Ab initio calculations were used to analyze interactions of with 1–4 molecules of NH3 at the MP2/6-311++G(d,p) and the B3LYP/6-311++G(d,p) computational levels. In addition to H3B–H⋯H–NH2 dihydrogen bond, the H2N–H⋯NH3 hydrogen bonds were also predicted in clusters. Negative cooperativity in clusters constructed from mixed H3B–H⋯H–NH2 dihydrogen and H2N–H⋯NH3 hydrogen bonds are more remarkable. The negative cooperativity increases with size and number of hydrogen bonds in cluster. The B–H stretching frequencies show blue shifts with respect to cluster formation. Greater blue shift in stretching frequencies was predicted for B–H bonds which did not contribute to dihydrogen bonding with NH3 molecules. The structures were analyzed with the atoms in molecules (AIM) methodology.